2013
DOI: 10.1038/jcbfm.2012.194
|View full text |Cite
|
Sign up to set email alerts
|

Mild Hypercholesterolemia Blunts the Proinflammatory and Prothrombotic Effects of Hypertension on the Cerebral Microcirculation

Abstract: Although an increased leukocyte and platelet adhesion is observed in cerebral venules of mice with either hypertension (HTN) or hypercholesterolemia (HCh), it remains unclear whether the combination of HTN and HCh exerts a comparable effect on leukocyte and platelet recruitment in the cerebral microvasculature. Thus, we examined whether HCh alters platelet and leukocyte adhesion, and blood-brain barrier (BBB) permeability, in cerebral venules in two models of murine HTN: DOCA salt-induced and angiotensin II (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…35 Twenty-four hours later, 0.4 mL of blood was obtained by cardiac puncture. Then, the mouse was transcardially perfused with phosphatebuffered saline (100 mmHg) for 5 min.…”
Section: Blood-brain Barrier Dysfunctionmentioning
confidence: 99%
“…35 Twenty-four hours later, 0.4 mL of blood was obtained by cardiac puncture. Then, the mouse was transcardially perfused with phosphatebuffered saline (100 mmHg) for 5 min.…”
Section: Blood-brain Barrier Dysfunctionmentioning
confidence: 99%
“…Hypertension induced in mice was accompanied by increased leukocyte and platelet adhesion in cerebral venules and was attenuated by mild hypercholesterolemia [11*]. Using mice with transgenic expression of apoA-I and wild-type mice treated with 4F suggested that the beneficial effect of the mild hypercholesterolemia was HDL-mediated [11*].…”
Section: Efficacy Of Apolipoprotein Mimetics In Models Of Diseasementioning
confidence: 99%
“…Using mice with transgenic expression of apoA-I and wild-type mice treated with 4F suggested that the beneficial effect of the mild hypercholesterolemia was HDL-mediated [11*]. …”
Section: Efficacy Of Apolipoprotein Mimetics In Models Of Diseasementioning
confidence: 99%
“…While it might be expected that risk factor combinations would exert an additive or synergistic effect on the vessel dysfunction elicited by the presence of individual risk factors, recent studies from our laboratory have revealed that mild diet-induced hypercholesterolemia blunts the recruitment of adherent leukocytes and platelets in venules, and protects against the impaired endothelium-dependent dilation in arteries elicited by hypertension(18, 22). It remains unclear whether this protective effect of HCh on HTN-induced vascular dysfunction is also manifested in genetically hypercholesterolemic (e.g, ApoE −/− ) mice placed on a normal diet.…”
Section: Introductionmentioning
confidence: 99%